The Development of Web-Based Image Puzzle Media for Madrasah Tsanawiyah Students - Tarigan, Nur Rizky; Ahkas, Akmal Walad (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
One of the learning media which can be used in mufrodat learning (Arabic vocabulary) is a web-based image puzzle. However, in reality, the educator that uses web-based learning media in learning Arabic still needs to be found. This research is development research (RnD) which aims to develop web-based image puzzle media for mufrodat learning (Arabic vocabulary) for VIII grade of MTs students and determine its feasibility through validation and practicality tests. The research model uses a 4-D model that has been modified to 3-D, which is divided into three stages; define (definition), design (design), and development (development). The research instruments include validation sheets to measure product feasibility, interviews with subject teachers, and student response questionnaires to measure the level of product practicality. Web-based image puzzle media obtains a score of 3.5 in material validation and a score of 3.6 from media validation that meets the valid category. Based on the student response questionnaire, web-based image puzzle media obtains a practicality percentage of 76% which categorizes in the excellent category. Therefore, web-based image puzzle media in mufrodat learning (Arabic vocabulary) can be feasible and practical for the learning process.